Real-time 3D measurement system for micro-manipulation. (2018) - Ohara, Kenichi; Takagi, Shota; Kojima, Masaru; Horade, Mitsuhiro; Kamiyama, Kazuto; Mae, Yasushi; Arai, Tatsuo
Construction of an activated three-dimensional (3D) tissue outside the human body is highly desirable, and it is expected that micro-manipulation should be used to construct 3D organisations. In micro-manipulation, it is difficult to obtain depth information, as an object is usually observed using an optical microscope. Thus, empirical techniques that require extensive practice are employed. To overcome this problem, a system that can perform real-time 3D measurements is indispensable. In this study, an improvement in the speed of 3D measurements in a microhabitat is obtained, which would facilitate micro-manipulation and the construction of 3D cellular organisations.